Phosphorus remobilization from rice flag leaves during grain filling: an RNA-seq study - Jeong, Kwanho; Baten, Abdul; Waters, Daniel L. E.; Pantoja, Omar; Julia, Cecile C.; Wissuwa, Matthias; Heuer, Sigrid; Kretzschmar, Tobias; Rose, Terry J. (Wiley, 2017)
The physiology and molecular regulation of phosphorus (P) remobilization from vegetative tissues to grains during grain filling is poorly understood, despite the pivotal role it plays in the global P cycle. To test the hypothesis that a subset of genes involved in the P starvation response are involved in remobilization of P from flag leaves to developing grains, we conducted an RNA‐seq analysis of rice flag leaves during the preremobilization phase (6 DAA) and when the leaves were acting as a P source (15 DAA). Several genes that respond to phosphate starvation, including three purple acid phosphatases (OsPAP3, OsPAP9b and OsPAP10a), were significantly up‐regulated at 15 DAA, consistent with a role in remobilization of P from flag leaves during grain filling. A number of genes that have not been implicated in the phosphate starvation response, OsPAP26, SPX‐MFS1 (a putative P transporter) and SPX‐MFS2, also showed expression profiles consistent with involvement in P remobilization from senescing flag leaves. Metabolic pathway analysis using the KEGG system suggested plastid membrane lipid synthesis is a critical process during the P remobilization phase. In particular, the up‐regulation of OsPLDz2 and OsSQD2 at 15 DAA suggested phospholipids were being degraded and replaced by other lipids to enable continued cellular function while liberating P for export to developing grains. Three genes associated with RNA degradation that have not previously been implicated in the P starvation response also showed expression profiles consistent with a role in P mobilization from senescing flag leaves.